Bird diversity and noteworthy records from the western side of the Porculla Pass and the Huancabamba-Chamaya river sub-basin, northwest of Peru - Saldaña, Irwing S.; Maria Koepcke Lab of Ornithology, Centro de Investigación en Biología Tropical y Conservación – CINBIOTYC, Piura, Perú (2020)
Despite the great importance of the level of biodiversity and endemism that theEquatorial Seasonal Tropical dry Forest hosts, many of its areas remain unexplored. Here wepresent the results of the field evaluations carried out between 2014 and 2018 along the westernside of the Porculla pass and the Huancabamba-Chamaya river sub-basin, in the northwest of Peru.this research is part of the dataset of the project Bird Assessments in Ecosystems of the Northwestof Peru – CINBIOTYC. We reported 174 bird taxa, belonging to 163 species and 32 families. Likewise,we reported two migratory bird species, one boreal and one austral, six endemics of Peru, and 31restricted-range species, from which 25 belong to the Tumbesian Region, seven to the MarañónValley and one was shared between them. We highlighted the record of four trans-Andean birdtaxa, Amazilia amazilia leucophoea, Euphonia saturata, Basileuterus trifasciatus, and Pyrocephalusrubinus piurae, as well as, the remarkable records of Patagioenas oenops, Thamnophilus shumbae,Pachyramphus spodiurus, Turdus maranonicus, and Incaspiza ortizi.